IDENTIFICATION AND QUANTIFICATION OF RELATED SUBSTANCES OF VITAMIND3 IN ITS PREPARTIONS BY RP-HPLC - Shah, Syed; M., Archana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
An analytical approach for quantifying vitamin D3 related substancesmethod was developed by using high-performance liquid chromatography (HPLC). The separation was achieved using a hypersil Silica, 250mm x 4.6mm, 5µm column, and a mobile phase composition of n-pentanol and n-hexane was used. The wavelength of the chromatogram was 265 nm at a temperature of 20℃, the flow rate was 2.0 mL/min. The method was specific, and linear within the range of 50%-150% and has demonstrated good recovery, inter day and intraday precision. As well as robustness, the detection and quantification limits were found to be within the limits at .001 and 0.0037 g/ml, respectively. The developed method ismore precise, accurate, specific and robust to determine the related substances of Vitamin D3 in its preparations and validated according to ICH guidelines Q2(R1).